2021
DOI: 10.1029/2020jb020850
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, Coeval Silicic Magma Storage Domains Beneath the Laguna Del Maule Volcanic Field Inferred From Gravity Investigations

Abstract: The rhyolite‐producing Laguna del Maule volcanic field (LdMVF), Chile, has had numerous post‐glacial eruptions that produced large explosions and voluminous lava flows. During the Holocene ∼60 m of surface uplift is recorded by paleo‐shorelines of the fresh‐water Laguna del Maule, with an inflation source near the Barrancas volcanic complex. Rhyolites from the Barrancas complex erupted over ∼14 ka including some of the youngest (1.4 ± 0.6 ka) lava flows in the field. New gravity data collected on the Barrancas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
(259 reference statements)
0
10
0
Order By: Relevance
“…Since 2007, widespread deformation 38 , 39 at rates greater than 20 cm/year 40 have been observed and modelled by an inflating sill 41 , 42 at about 3 km below sea level (5 km below surface). The field is characterized by a 19 mGal Bouguer gravity low, centred over the deformation source, caused by a shallow, crystal-poor, volatile-rich, silicic magma system overlying the sill 43 , 44 .
Figure 6 Location of LdMvf.
…”
Section: Resultsmentioning
confidence: 99%
“…Since 2007, widespread deformation 38 , 39 at rates greater than 20 cm/year 40 have been observed and modelled by an inflating sill 41 , 42 at about 3 km below sea level (5 km below surface). The field is characterized by a 19 mGal Bouguer gravity low, centred over the deformation source, caused by a shallow, crystal-poor, volatile-rich, silicic magma system overlying the sill 43 , 44 .
Figure 6 Location of LdMvf.
…”
Section: Resultsmentioning
confidence: 99%
“…Their model suggests a depth to basement of around 3 (±0.5) km within the caldera. Seebeck et al (2010) concluded that a magma body at 6 km depth beneath the OVC was likely undetectable, however the assumption of a rhyolitic magma body having a density contrast of only − 0.300 g/cm 3 (2.470 g/cm 3 absolute) likely significantly underestimates the density contrast of magma found at similar silicic centers, that may be up to 0.7 g/cm 3 (absolute 1.9 g/cm 3 ) when the magmatic volatile phase is taken into account (e.g Miller et al, 2017;Trevino et al, 2021).…”
Section: Previous Geophysical Studiesmentioning
confidence: 99%
“…While gravity modeling is mathematically non-unique (LaFehr and Nabighian, 2012), at Uturuncu we have a wealth of geophysical (Jay et al, 2012;Ward et al, 2014;Comeau et al, 2016;Kukarina et al, 2017;Hudson et al, 2021) and petrological (Sparks et al, 2008;Muir et al, 2014b;Muir et al, 2014a;Muir et al, 2015) information to constrain our modeling. When used in conjunction with other data sets, gravity measurements can be a powerful tool for understanding complex volcanic structures (Trevino et al, 2021), highlighting features other methods may be blind to. A density model of the upper 10 km at Uturuncu of comparable resolution to the existing resistivity model could falsify or support the presence of saline fluids at Uturuncu and their contribution to the deformation signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, these three scenarios would have quite different densities, with the potential to falsify any one of these hypotheses. Gravity surveys have imaged subsurface density structure at multiple volcanic systems (Zurek and Williams-Jones, 2013;Young et al, 2020;Trevino et al, 2021). A gravity inversion by del Potro et al (2013) revealed a ca 15 km wide low density column rising from the APMB beneath Uturuncu, but this model lacks sufficient resolution to compare with the low resistivity anomalies Comeau et al (2016) imaged in the upper 10 km.…”
Section: Introductionmentioning
confidence: 99%